The Issues of Wa'ad IMBT in The Fatwa DSN MUI Based on Fiqhiyyah Rules - Rahman, Muh Fudhail; Luhur, Mujhid Budi (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2021)
Abstract. This study discusses the concept and function of wa'ad in the DSN-MUI Fatwa No.85/DSN-MUI/XII/2012 concerning Wa'ad in Islamic Financial and Business Transactions, changing the contract from non-binding to binding nature. This study aims to analyze wa'ad law in IMBT in terms of its risks and benefits. This study uses data from the DSN-MUI Fatwa, Islamic jurisprudence, and other scientific papers. This study finds out that IMBT combines an ijarah contract (lease) with a sale-purchase contract or a grant. The ijarah contract, the sale, and the purchase contract are linked with an agreement. In principle, the legal status of fulfilling wa'ad in Islamic finance and business transactions is binding because it will provide benefits for the Islamic economic community, and there will be no financing problems. In the DSN-MUI fatwa, the concept of "Doing two lesser evils" is used in determining the fatwa regarding promises (wa'ad) in a transaction.Keywords: Wa'ad, IMBT, Binding Promise, Islamic Jurisprudence Abstrak. Kajian ini membahas tentang konsep dan fungsi wa’ad dalam Fatwa DSN-MUI No.85/DSN-MUI/XII/2012, yang diubah dari tidak mengikat menjadi mengikat. Penelitian ini bertujuan untuk mengetahui analisis hukum wa’ad dalam IMBT ditinjau dari sisi kemaslahatan dan risikonya. Metode yang digunakan dalam penelitian ini adalah metode yuridis normative, dengan data berupa Fatwa DSN-MUI, literatur Hukum Islam/Fiqh, dan karya ilmiah lainnya. IMBT merupakan gabungan antara akad ijarah (sewa) dengan akad jual beli atau hibah. Akad ijarah dan akad jual beli  diikat dengan janji. Pada prinsipnya status hukum pemenuhan janji (wa’ad) dalam transaksi keuangan dan bisnis syariah adalah mengikat karena akan memberikan manfaat bagi masyarakat ekonomi syariah dan tidak menimbulkan masalah pembiayaan. Pada fatwa DSN-MUI, konsep “Melakukan dua keburukan yang lebih ringan” digunakan dalam menentukan fatwa tentang janji (wa’ad) dalam suatu transaksi.  Kata Kunci: Wa'ad, IMBT, Janji Yang Mengikat, Aturan Fiqhiyyah